Cardiac involvement in COVID-19: a matter close to the heart, beyond the acute illness - Oliveira, Gláucia Maria Moraes de (2023)
© 2023 International Journal of Cardiovascular Sciences. This is an Open Access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.